Perancangan Aplikasi Berbasis Web Dengan User-Centered Design Untuk Mengukur Mutuality Dan Family Resilience Pada Caregiver - Febtriko, Anip; Afriyeni, Nelia; Rahayuningsih, Tri (JurTI (Jurnal Teknologi Informasi), 2024)
The role of caregivers in providing care to individuals with special needs, such as the elderly or patients with chronic conditions, is often accompanied by complex psychological challenges. To support caregiver well-being, measuring mutuality and family resilience is important as an indicator of emotional relationships and family adaptability. This study aims to design a web-based application to measure mutuality and family resilience using a user-centered design (UCD) approach, which focuses on user needs and experiences. The research method includes four main stages: (1) needs analysis through interviews with caregivers and psychologists to understand measurement needs, (2) designing an application prototype with UCD principles, (3) evaluating the design using the usability testing method, and (4) initial testing of the reliability and validity of the psychological measurements applied in the application. This platform is equipped with a psychometric-based questionnaire feature, easy-to-understand measurement result reports, and recommendations for further support. The results of the study indicate that this application is effective in providing measurement tools that are easy to use by caregivers. Usability testing resulted in a user satisfaction score of 85%, indicating an intuitive and appropriate interface. In addition, initial testing of the instrument's validity showed good consistency in measuring mutuality and family resilience. In conclusion, this application can be a useful tool in supporting caregiver well-being, with the potential for wider application in family or community contexts. Further research is needed to develop additional features and increase the scale of implementation.